PEMBERDAYAAN SUMBER DAYA SANTRI MELALUI ENTREPRENEURSHIP DI PONDOK PESANTREN AL-ASHRIYYAH NURUL IMAN ISLAMIC BOARDING SCHOOL PARUNG-BOGOR - Prayitno, Prima (QUALITY, 2016)
This research is to know the santri resource empowerment through entrepreneurship in Islamic boarding school of Al Ashriyyah Nurul Iman Parung Bogor. The type of this research is field research with qualitative approaches. The location of this study is in the Islamic boarding school of al-Ashriyyah Nurul Iman Parung Bogor. The data collection was done by direct observation, formal and informal interviews, and documentation. The validity of the data was tested with triangulation of technique, source, and time. In analyzing the data used an interactive data analysis; they are data reduction, the data presentation and the conclusion withdrawal. The results of this study showed that (1) in the empowerment, the students who have finished their study as an undergraduate are required to serve for two years. In the stage of empowerment through input, implementation process and output, (2) the three elements they are education, entrepreneurship field, and entrepreneurial fields that exist in the Islamic boarding school is a unity that cannot be separated. The management activities starting from the planning, organization, direction, and control (3) Factor constraints that impede of entrepreneurial activity did by every unit such as: the existence of tool damage for the production implementation. In carrying out the stuff that hasn't been realized because there is more preferred Islamic boarding school’s needs, environmental factors both internally and externally, while the supporting factors are: santri resource satisfy, devotion sincere intention, leader and Kyai motivation, proud with the results of his own works, enough infrastructure.